2009
DOI: 10.1080/10408440802475199
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the cancer potential of methanol

Abstract: There are no published cancer studies of methanol-exposed cohorts. Genotoxicity studies do not suggest carcinogenic activity from methanol exposure. Oncogenicity studies of methanol were conducted by inhalation for approximately 20 hrs/day at up to 1000 ppm in F344 rats and B6C3F1 mice (NEDO), and by incorporation into drinking water at up to 20,000 ppm in Sprague-Dawley rats (Ramazzini Foundation, by Soffritti et al.). No increased neoplasms were found in the NEDO rat and mouse inhalation studies, even at air… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
32
0
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 31 publications
0
32
0
3
Order By: Relevance
“…The spontaneous (control) rate of these tumors in RI Sprague-Dawley rats has been reported to be higher than in Sprague-Dawley rats from other sources (Cruzan 2009). Using the meta-regression technique of Sidik and Jonkman (2005), we performed an analysis of past RI studies (see Supplemental Material, Table S1) and identified a significant association between spontaneous lymphoma/leukemia rates and year of study publication for both males and females ( p < 0.001).…”
Section: Considerations For Existing Ri Cancer Bioassaysmentioning
confidence: 97%
See 3 more Smart Citations
“…The spontaneous (control) rate of these tumors in RI Sprague-Dawley rats has been reported to be higher than in Sprague-Dawley rats from other sources (Cruzan 2009). Using the meta-regression technique of Sidik and Jonkman (2005), we performed an analysis of past RI studies (see Supplemental Material, Table S1) and identified a significant association between spontaneous lymphoma/leukemia rates and year of study publication for both males and females ( p < 0.001).…”
Section: Considerations For Existing Ri Cancer Bioassaysmentioning
confidence: 97%
“…Concurrent RI studies have at times shared controls (Belpoggi et al 1995; Cruzan 2009), with RI publications indicating that such shared controls have been concurrent with, housed in the same facility as, and age-, strain- and colony-matched to treatment groups (Maltoni et al 1986, 1999; Soffritti et al 2002c, 2006a). U.S. EPA testing guidelines require (U.S.…”
Section: Considerations For Existing Ri Cancer Bioassaysmentioning
confidence: 99%
See 2 more Smart Citations
“…9 We consider it in the public interest to promote resolution of the scientific questions that have been raised about the methanol and other bioassays. 2,4,[6][7][8][10][11][12][13]15,16 We therefore obtained the results of the slide review from the National Institute of Environmental Health Sciences via a Freedom of Information Act request and analyzed them for differences between the NTP pathologists' diagnoses and those of the study pathologist. We tabulated diagnoses of lymphoma, leukemia, and histiocytic sarcoma in thymus, lung, liver, spleen, and lymph nodes and inflammatory lesions in the nose, lung, and ear.…”
mentioning
confidence: 99%